Tactical publishing : Using Senses, Software, and Archives in the Twenty-First Century - Ludovico, Alessandro; Montfort, Nick (Cambridge, Massachusetts : The MIT Press, 2023)
"Tactical Publishing explores new experimental ways of publishing investigating historical, artistic and technical precedents to provide a new evolution of publishing"--
boek